Ethiopian EFL teachers’ classroom practice and learners’ view on teaching and learning English speaking skill - Dereje Asfaw Bulbula; Obsa Neme; Tesfa Alemu; Mulualem Getachew; Fedila Abazinab; Damtew Bulbula (Association for Scientific Computing Electrical and Engineering(ASCEE), 2023)
Communication capacity (Speaking skill) in English language education is a difficult task that needs effective guidance and sustainable practice. Therefore, this study aimed at exploring the Implementation of Teaching and Learning English Speaking Skills in Ethiopian EFL Classes. The design of the study was descriptive survey. There were 523 students included using a simple random sampling technique and 30 EFL teachers using an availability sampling technique. To collect data, questionnaire for students and Focus Group Discussions for teachers were used. Mixed method data analysis was used. The results showed that EFL teachers were not using different techniques to teach English speaking skills, and they were not making sustainable follow-ups on how learners performed. They also apply the teacher-centered method rather than the learner’s method. Learners face challenges from their mother tongue's influence, lack of confidence, and fear of making a mistake. EFL teachers were also challenged by student-related problems like being disinterested in being involved in the actual teaching and learning actively, uncomfortably of the school compound, absence of well-equipped English mini-media, and the bulkiness of the textbook. Thus, EFL teachers should use various techniques, school administration should avail the resource and students should be participatory in their learning.